PsycEXTRA Dataset 2004
DOI: 10.1037/e446042005-001
|View full text |Cite
|
Sign up to set email alerts
|

"The Behavioral Effects of Environmental Enrichment in Rats"

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 81 publications
(203 reference statements)
4
9
0
Order By: Relevance
“…Similar studies in the research literature, which reported statistically significant effects, had cell sizes of 7 -12 animals for enrichment (e.g., Van Praag et al, 1999;Elliott & Grunberg, 2005;Tomchesson, 2004). Mering Kaliste-Korhonen and Nevalainen (2000) determined that 5 -10 animals were needed to find statistically significant effects for enrichment on various biological measures including body weight and fat/adipose tissue.…”
Section: Experimental Design and Determination Of Sample Sizementioning
confidence: 51%
See 4 more Smart Citations
“…Similar studies in the research literature, which reported statistically significant effects, had cell sizes of 7 -12 animals for enrichment (e.g., Van Praag et al, 1999;Elliott & Grunberg, 2005;Tomchesson, 2004). Mering Kaliste-Korhonen and Nevalainen (2000) determined that 5 -10 animals were needed to find statistically significant effects for enrichment on various biological measures including body weight and fat/adipose tissue.…”
Section: Experimental Design and Determination Of Sample Sizementioning
confidence: 51%
“…In addition, a variety of objects (durable toys including colored textured balls, rings, and bones) were placed in the cage to provide physical and tactile stimulation. This particular enriched environment has been effective in previous experiments in our laboratory assessing environmental effects on performance and activity (Elliott, 2004;Tomchesson, 2004 (Sclafani & Springer, 1976;Bowling, Rowlett, & Bardo, 1993;Hellemens et al, 2004 …”
Section: Environmental Enrichment (Ee)mentioning
confidence: 99%
See 3 more Smart Citations